The Eastern Door Center: re-balancing the wheel–a Two-Eyed Seeing approach to FASD and other disorders related to transgenerational adversity - Cox, Lori Vitale (Frontiers in Sociology, 2023)
In 2015, the Canadian Truth and Reconciliation Commission called for immediate action to address the lack of access to health services for Fetal Alcohol Spectrum Disorder (FASD) in Indigenous communities. In their Calls to Action, the TRC called for the provision of culturally safe, community-based, FASD diagnosis intervention and prevention services. (TRC 2015) FASD is a neurodevelopmental condition that can affect all aspects of functioning. The term refers to a spectrum of conditions occurring as a result of prenatal exposure to alcohol (PAE). PAE can affect both physical and mental health leading to problems with learning, memory, attention, language, social behaviour, executive functioning, sleep, and affect regulation. According to Elders in M’ikmaq First Nations (FN) communities, FASD is a condition that is rooted in transgenerational trauma and the loss of relationship to their land, their language and the traditional community culture. The Elsipogtog Eastern Door (ED) Centre opened in 2006 to provide culturally informed diagnosis, intervention and prevention for FASD and related conditions. The ED was the first FASD diagnostic team in Atlantic Canada and it served as a demonstration model for the New Brunswick FASD Centre of Excellence as well as for Indigenous communities regionally and nationally (Clairmont 2010). In this article, we outline the history and evolution of the Eastern Door Center and its programs and describe some of the successes of this model as well as some of its limitations in practice